Conference Evaluation Focusing on Learning and Transfer - Michael Andersen; Bjarne Wahlgren (Journal of MultiDisciplinary Evaluation)
Background: The article presents the results of using a model for evaluation of conferences; a model focusing on learning and transfer. Many conferences are evaluated using participant-satisfaction surveys, but satisfaction is a diffuse concept and is linked to many factors other than learning.